2017
DOI: 10.1049/iet-rpg.2016.0904
|View full text |Cite
|
Sign up to set email alerts
|

Power system stability analysis under increasing penetration of photovoltaic power plants with synchronous power controllers

Abstract: The utilization of renewable sources brings many benefits to electric power systems, but also some challenges like the impact that renewable power plants employing power electronics have on the grid, which is gaining importance as the penetration of this type of generating stations increases, driven by the construction of large wind or solar photovoltaic power plants. This paper analyses the impact of large-scale photovoltaic power plants on a transmission grid for different penetration levels. The analysis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 36 publications
0
55
0
1
Order By: Relevance
“…Since existing synchronous generators are decreasing their power production with the increased penetration of photovoltaic (PV) generation at distribution systems, the impact on their voltage stability has become non-negligible and more analysis is needed [1,2]. Reviewing research literature shows that they have focused on the impact of solar-PV generation on short-and long-term voltage stability [3,4]. Developing studies conduct an investigation into the effect of these systems on power distribution systems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Since existing synchronous generators are decreasing their power production with the increased penetration of photovoltaic (PV) generation at distribution systems, the impact on their voltage stability has become non-negligible and more analysis is needed [1,2]. Reviewing research literature shows that they have focused on the impact of solar-PV generation on short-and long-term voltage stability [3,4]. Developing studies conduct an investigation into the effect of these systems on power distribution systems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The SPC has been widely used to enable electronics power converter to behave as a synchronous machine [29][30][31][32], being an interesting control solution to implement virtually synchronous FACTS. In contrast to PLL-based conventional control schemes, the SPC relies on a power balancing mechanism to maintain its synchronism with the electrical grid.…”
Section: Synchronous Power Controllermentioning
confidence: 99%
“…In addition, authors in [5] indicated that higher PV penetration induces dramatic frequency oscillation beyond grid operating standards that potentially threatens uninterrupted load supply. Power oscillation damper [6], synchronous power controller [7], [8] and multiple-model adaptive control strategy [9] is adopted at PV terminal to damp out power system oscillations resulted from temporary power imbalances and maintain robust damping performance. A droop-type control [10], synthetic inertia control [11] and operating point lower than maximum power point (MPP) [12] are proposed to regulate PV power output and contribute in system frequency regulation.…”
Section: Introductionmentioning
confidence: 99%